(untitled) (International conference on multidisciplinary science, 2025)
Stress, both acute and chronic, has a profound impact on cardiovascular regulation. The body’s response to stress involves complex neurohumoral mechanisms that adjust heart rate, blood pressure, and vascular tone to maintain homeostasis. During acute stress, sympathetic nervous system activation leads to increased cardiac output and peripheral vasoconstriction, preparing the body for a "fight or flight" reaction. Chronic stress, however, induces sustained neuroendocrine responses, especially via the hypothalamic-pituitary-adrenal (HPA) axis, resulting in elevated cortisol levels and long-term alterations in vascular reactivity and endothelial function.These changes, if persistent, may lead to hypertension, atherosclerosis, and an increased risk of cardiovascular events such as myocardial infarction and stroke. Recent studies highlight the importance of stress management in preventing cardiovascular disease. This article explores the physiological background of cardiovascular control mechanisms under stress, analyzes acute versus chronic responses, and discusses clinical correlations with recent research data and potential preventive approaches.